Development of the oppression-based traumatic stress inventory: a novel and intersectional approach to measuring traumatic stress - Holmes, Samantha C.; Zalewa, Daniel; Wetterneck, Chad T.; Haeny, Angela M.; Williams, Monnica T. (Frontiers in Psychology, 2023)
There is a growing body of literature demonstrating that experiences of oppression (e.g., racism, sexism, heterosexism, poverty) are associated with posttraumatic stress disorder symptoms. Traditional trauma assessments do not assess experiences of oppression and it is therefore imperative to develop instruments that do. To assess oppression-based traumatic stress broadly, and in an intersectional manner, we have developed the oppression-based traumatic stress inventory (OBTSI). The OBTSI includes two parts. Part A comprises open-ended questions asking participants to describe experiences of oppression as well as a set of questions to determine whether Criterion A for PTSD is met. Part B assesses specific posttraumatic stress symptoms anchored to the previously described experiences of oppression and also asks participants to identify the various types of discrimination they have experienced (e.g., based on racial group, sex/gender, sexual orientation, etc.). Clients from a mental health clinic and an undergraduate sample responded to the OBTSI and other self-report measures of depression, anxiety, and traditional posttraumatic stress (N = 90). Preliminary analyses demonstrate strong internal consistency reliability for the overall symptom inventory (α = 0.97) as well as for the four symptom clusters of posttraumatic stress symptoms in the DSM-5 (α ranging from 0.86 to 0.94). In addition to providing descriptive information, we also assess the convergent validity between the OBTSI and measures of anxiety, depression, and traditional posttraumatic stress and examine the factor structure. This study provides preliminary evidence that the OBTSI is a reliable and valid method of assessing oppression-based traumatic stress symptoms.